Psychological perspectives on children's spirituality - Nye, Rebecca (1998)
There have been very few attempts to understand the nature of children's spirituality which have undertaken a study of children themselves. More often this topic has been examined through the various perspectives provided by religious, moral, educational and generally adult agenda. This thesis offers a study of children's spirituality drawing on perspectives from developmental psychology. Its intention is to make a distinctive theoretical contribution towards an understanding of children's nature. The methodological approach is that of an empirical, qualitative investigation and analysis. The main data presented are interviews conducted with six and ten year old children in which the opportunity to discuss potentially spiritual experiences, feelings, and issues was encouraged. Chapter 1 explores the history of interest in spirituality reflected in education policy documents, as well as a selective review of the scholarly education literature this has increasingly inspired. Chapter 2 explores the nature of a psychological contribution. Although the spiritual has rarely found an established place in psychology's research agenda, I offer a compilation of relevant exceptions to this neglect. These are drawn both from explicit attempts by psychologists to investigate discrete aspects of children's religious lives, as well as from psychological models of development in which the nature of children's spirituality is more implicitly suggested. The development of a provisional conceptual framework specifically for children's spirituality (particularly the empirical study of it) is outlined in chapter 3. A variety of psychological scholarship is used to inform this framework, as is a discussion of the complexities affecting the definition of spirituality in a contemporary context. Since few empirical studies have been conducted in this area, the methodological approach devised for this study is described in detail. Considerable attention is given to the foundational issue of the researcher's perspective, as well as the procedural stages from piloting to data analysis. Chapters 5 and 6 offer my interpretative analyses. I describe how repeated qualitative analysis was essential to uncovering layers of meaning in the data, and how this gradually gave way to an interpretative account of children's spirituality expressed in broadly psychological terms. I propose that much of the nature of children's spirituality may be described in terms of a demonstration of a particular kind of consciousness, referred to here as 'relational consciousness'. This core category is further explored in terms of its contributory dimensions, drawing on a coding paradigm suggested by grounded theory methodologists. The final chapter considers additional psychological parallels which this new description of children's spirituality affords, and the more general implications of this work for children's education. It is suggested that the conduct of the study as a whole in terms of its literature research, method, data and analytical framework, demonstrates the potential of pursuing a psychologically informed approach in this area.